(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Managing of abortion is an important subject in gynecology. Millions of patients had sufferedfrom spontaneous abortions that occur per year.Objectives: The aim of this study was to compare the effect of misoprostol alone and misoprostol withletrozole in the induction of abortion in the first trimester of pregnancy.Patients and Methods: In a single –blind clinical trial ,128 female applicants for legal abortion within thefirst trimester of pregnancy that referred to AL-Batool hospital , were divided in to two groups: intervention(misoprostol with letrozole) and control groups (misoprostol alone). The complete abortion, drug-inducedside effects of misoprostol and letazole were noted and evaluated.Results: The complete abortion rate was93.2% in intervention group and in68.7% in the control group(misoprostol) only, which was significantly higher in intervention group (p = 0.001).Abdominal pain in the intervention group is also significantly lower than that of the control group (p =0.013). Intervention group also had significantly lower duration of bleeding rather than control group (p =0.006).Conclusions: Based on our results, pretreatment with letrozole plus Misoprostol was more effective forprompting abortion in the first trimester of pregnancy without increasing side effect compared to misoprostolalone.